Alternating Current Electric Field Driven Topologically Defective Micro/nanomotors. (March 2022) - Zhuang, Rencheng; Zhou, Dekai; Chang, Xiaocong; Mo, Yi; Zhang, Guangyu; Li, Longqiu
Highlights: A new type of electric-driven micro/nanomotors with topologically defective shapes is proposed. The defective golden micro/nanomotors (DGMs) can overcome the constraints of the substrate and the 3D helical motion in terms of asymmetric shapes is first reported. The propulsion mechanisms of the DGMs are clarified and the DGMs show highly controllable cargo transportation capability. Abstract: Design and synthesis of electric-driven micro/nanomotors (EDMNMs) have attracted tremendous attention because of their unique advantages, such as non-necessity of fuel, high mobility, and flexible controllability. However, existing EDMNMs are mostly Janus structures based on two hemispheres made from heterogeneous materials. Here, we propose a new type of defective electric-driven micro/nanomotor with an asymmetric shape. It is found, for the first time, that the defective golden micro/nanomotors (DGMs) can generate a locally asymmetric field gradient through the topological defect, and can achieve controllable self-dielectrophoresis (sDEP) and induced-charge electrophoresis (ICEP) motion behaviors in different frequency ranges. In particular, the DGMs can achieve three-dimensional helical motion behavior through designing their defective structure. Furthermore, we demonstrate that the DGMs can attract or repel cargos under different electric frequencies. These new DGMs and their attractive performance pave the way for fabricating highly controllable EDMNMs via structural design and can be widely applied in biomedicine, micro/nanosensors, and micro/nanomechanical systems. Graphical Abstract: Image, graphical abstract